Saidaiji Monks and Esoteric Kami Worship at Ise and Miwa - Andreeva, Anna (Japanese journal of religious studies, 2006)
By the eighth century, Mount Miwa, the most important site of worship connected to the early Yamato ruling houses in prehistoric times, had gradually become "de-sacralized" and "forgotten" by imperial family in favor of Ise. In the course of the thirteenth and fourteenth centuries it was rediscovered and reinvented by Buddhist lineages who aimed to restore the proper monastic order in a time of mappō and to protect the state and the "divine land" of Japan in the wake of the Mongol invasions. The outcome of this was the phenomenon of Miwa(ryū) Shintō, a type of kami worship that has later been categorized as one of the traditions of esoteric Shinto or the "Shinto of Two Realms" (Ryōbu Shintō). It is thought to have developed in the vicinity of Mount Miwa during the early medieval period, and is often mentioned in connection with the Saidaiji lineage which participated in the revival of monastic precepts in thirteenth century Japan. It has also been assumed that Eizon (1201-1290), an esoteric master and a central figure to the precept revival movement, played a defining role in the ritualism of the emerging esoteric kami worship at Miwa. The question remains, however, as whether these phenomena were really connected and why Miwa attracted the attention of the Saidaiji lineage.